The Genetic Differentiation of Pyrrhulina (Teleostei, Characiformes) Species is Likely Influenced by Both Geographical Distribution and Chromosomal Rearrangements - Ferreira, Pedro H. N.; Souza, Fernando H. S.; de Moraes, Renata L.; Perez, Manolo F.; Sassi, Francisco de M. C.; Viana, Patrik F.; Feldberg, Eliana; Ezaz, Tariq; Liehr, Thomas; Bertollo, Luiz A. C.; Cioffi, Marcelo de B. (Frontiers in Genetics, 2022)
Allopatry is generally considered to be one of the main contributors to the remarkable Neotropical biodiversity. However, the role of chromosomal rearrangements including neo-sex chromosomes for genetic diversity is still poorly investigated and understood. Here, we assess the genetic divergence in five Pyrrhulina species using population genomics and combined the results with previously obtained cytogenetic data, highlighting that molecular genetic diversity is consistent with their chromosomal features. The results of a principal coordinate analysis (PCoA) indicated a clear difference among all species while showing a closer relationship of the ones located in the same geographical region. This was also observed in genetic structure analyses that only grouped P. australis and P. marilynae, which were also recovered as sister species in our species tree analysis. We observed a contradictory result for the relationships among the three species from the Amazon basin, as the phylogenetic tree suggested P. obermulleri and P. semifasciata as sister species, while the PCoA showed a high genetic diversity of P. semifasciata to all other species. These results suggest a potential role of sex-related chromosomal rearrangements as reproductive barriers between these species.